Determinants of Diarrhea in Toddlers in the Work Area of ​​the Sapta Taruna Health Center in Pekanbaru City: Determinan Kejadian Diare Pada Balita Di Wilayah Kerja Puskesmas Sapta Taruna Kota Pekanbaru - Sindi Novia Safitri; Yuyun Priwahyuni; M. Kamali Zaman; Chirstine Vita G.P; Leon Chandra (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Diarrhea is a disease that causes sufferers to have frequent bowel movements with watery stools. Diarrhea can occur due to food and drink exposed to viruses, bacteria or parasites. Some of the common causes are infections by viruses, bacteria, and parasites, food poisoning, and side effects of drugs. This study aims to determine the determinants of the incidence of diarrhea in children under five in the working area of the Sapta Taruna Health Center. This type of research uses a quantitative analytic study with a cross sectional research design. The population is 1,737 respondents with a sample of 152 respondents using accidental sampling technique. The location of the research was carried out in the working area of the Sapta Taruna Health Center. The results of this study indicate the proportion of diarrhea in children under five is 22.4%. The determinants that have a relationship with the incidence of diarrhea in children under five are the provision of clean water (p value = 0.0001) with a POR value of 5.527, drinking water sources (p value = 0.012) with a POR value of 2.898, the availability of latrines (p value = 0.0001) with a POR value of 10.298, and hand washing habits (p value = 0.0001) with a POR value of 4.900. In conclusion, there is a significant relationship between the provision of clean water, drinking water sources, availability of latrines and hand washing habits with the incidence of diarrhea in the working area of the Sapta Taruna Health Center. It is recommended that the Puskesmas routinely provide counseling about nutrition, PHBS and diarrhea.